EFFICIENCY ANALYSIS OF MALAYSIAN FAMILY TAKAFUL USING STOCHASTIC FRONTIER APPROACH - Zubaidah Nasution; Labibah Salsabila; Surya Setiawan (Universitas Muhammadiyah Prof Dr Hamka, 2022)
Malaysia has the most extensive family takaful market with a growth rate of 16 percent in 2015. Takaful development in Malaysia should be assessed to govern better improvement especially for the insuranceindustry. This research aims to examine the efficiency level of 11 family takaful in Malaysia from 2017 to 2020 using Stochastic Frontier Approach (SFA) involving management expenses as an input, net benefits & claims, and investment income as output. The result showed that Malaysian family takaful is considered less efficient from 2017 to 2020, with production efficiency level average at 56.83 percent. The author finds that management expenses negatively affect investment income, while net benefits & claims give positive impact. However, both variables are not significant enough to influence investment income. Keywords: Malaysia, Efficiency Level, Stochastic Frontier Approach.